EFFECT OF OXYTOCIN ON SPERM FUNCTION AND SEMINALBIOCHEMISTRY OF ASTHENOSPERMIC PATIENTS - Al-Janabi, Adnan S; Al-Mehdawi, Ferial A; Al-Lami, Makarim Q (Al-Nahrain Journal of Science, 2009)
Semen samples of 90 asthenospermic patients were examined, then they were divided into three main equal groups. In the first group, Oxytocin (OT) addition in three concentrations (2, 4, and 6 IU/ml) with sperm preparation medium (SPM) to the semen samples was investigated. Changes in sperm function tests and seminal biochemistry was used as indicator of effect. Results indicated that a significant increase in sperm grade activity in 2 IU/ml OT with a tendency for a decrease in this motility parameter in higher OT concentration. Concentration 2 IU/ml of OT was applied with SPM and without in the second and third groups, respectively. In presence of SPM, a significant increase in the sperm motility characteristics (the percentage of sperm motility and sperm grade activity) was observed. While when SPM was absent, non-significant change in these parameters was seen. These findings indicate that OT at the concentration of 2 IU/ml has got a stimulatory effect on sperm motility characteristics. Using of SPM potentiated this effect of OT.Total protein (TP), cholesterol, calcium, creatine kinase (CK), and fructose were measured in the seminal plasma and in the supernatant of sperm suspension of OT-treated and control samples. According to the results, a high significant increase in cholesterol was found in the external medium, this may be attributed to loss of cholesterol from the plasma membrane of the sperm. Also, OT may modify cellular calcium transport across the plasma membrane, resulting in high intracellular calcium concentration and a high significant decrease in level of calcium in the external medium. In addition to a high significant decrease in fructose level of the external medium.